Revolutionizing Facilities: A Review Of Sustainable Building Operation And Maintenance Innovations In Tertiary Institutions - Mohd Mubarak Shamsuddin; Wan Norisma Wan Ismail; Fadli Arabi; Norsafiah Norazman; Marlya Dahuri; Mohd Asnawi Abd Wahab; Othman Talib (Global Academic Excellence (M) Sdn Bhd, 2026)
Indexed by MYCITE